2013
DOI: 10.1002/jcb.24620
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous polyamines promote osteogenic differentiation by reciprocally regulating osteogenic and adipogenic gene expression

Abstract: Polyamines are naturally occurring organic polycations that are ubiquitous in all organisms, and are essential for cell proliferation and differentiation. Although polyamines are involved in various cellular processes, their roles in stem cell differentiation are relatively unexplored. In this study, we found that exogenous polyamines, putrescine, spermidine, and spermine, promoted osteogenic differentiation of human bone marrow-derived mesenchymal stem cells (hBMSCs) without inducing cell death or apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…1). By analyzing both the catabolic and anabolic enzyme expression of polyamine biosynthesis, it is suggested that in the presence of exogenous polyamines, ODC was suppressed and SSAT was stimulated to prevent rapid increase in intracellular polyamines [24]. Conversely, SSAT was suppressed when hBMSCs were treated with DFMO or siODC possibly to prevent further depletion of the polyamine pool (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1). By analyzing both the catabolic and anabolic enzyme expression of polyamine biosynthesis, it is suggested that in the presence of exogenous polyamines, ODC was suppressed and SSAT was stimulated to prevent rapid increase in intracellular polyamines [24]. Conversely, SSAT was suppressed when hBMSCs were treated with DFMO or siODC possibly to prevent further depletion of the polyamine pool (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Primer sequences and conditions for real-time PCR analysis are the same as those reported previously [24].…”
Section: Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced SSAT activity affects osteoblastogenesis and seemed to be mediated through mechanisms other than polyamine depletion. (10) Here, monoclonal antibodies (mAbs) against SSAT were prepared to understand the molecular mechanisms underlying the complex roles of SSAT, and to find additional biological functions of this protein, as well as to investigate its mechanisms of action and how its levels of expression are regulated.…”
Section: Introductionmentioning
confidence: 99%